HAK ASASI MANUSIA: TINJAUAN DARI ASPEK HISTORIS DAN YURIDIS - Wilujeng, Sri Rahayu (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT This paper discusses the human rights based on the historical and legal standpoint. Historically, the human rights struggle in Indonesia appears during period the indegenous people against to oppression of the Colonial. The struggle to get independence essentially was the human rights enforcement. Legally, the human rights in Indonesia have the law basis through Ketetapan MPR no. XVII/MPR/ 1998 on Human Rights, and Undang Undang No. 39/ 2000 on Human Rights. Keywords: human rights, historical background, legal basis.